PENGARUH CURRENT RATIO (CR) DAN DEBT TO ASSET RATIO (DAR) TERHADAP NET PROFIT MARGIN (NPM) PADA PT ULTRAJAYA MILK INDUSTRI & TRADING COMPANY TBK PERIODE 2013-2022 - Ismiati Magdalena, Anggi; Nurmasari, Ifa (Journal of Research and Publication Innovation, 2024)
This research aims to examine the influence of Current Ratio (CR) and Debt To Asset Ratio (DAR) on Net Profit Margin (NPM) at PT Ultrajaya Milk Industri & Trading Company Tbk for the period 2013-2022. The research method used is a quantitative method with a descriptive approach . The data used is secondary data obtained from the financial reports of companies listed on the Indonesia Stock Exchange (BEI). The independent variables studied are Current Ratio (CR) and Debt To Asset Ratio (DAR) and the dependent variable is Net Profit Margin (NPM). The analysis results show that the Current Ratio (CR) and Debt To Asset Ratio (DAR) have a significant effect on Net Profit Margin (NPM). Based on the results of the simultaneous test (F Test) carried out, it can be concluded that the Current Ratio (CR) and Debt To Asset Ratio (DAR) have a significant influence on the Net Profit Margin (NPM) at PT Ultrajaya Milk Industri & Trading Company Tbk for the 2013- 2022. In addition, the coefficient of determination (R Square) of 59,1,% shows that the Current Ratio (CR) and Debt To Asset Ratio (DAR) variables are able to explain 59,1,% of the variations that occur in the Net Profit Margin (NPM) variable. . The remaining 40,9% is explained by other factors not examined in this study.